Kepastian Hukum terhadap Pengembalian dana Refund pasca Jual Beli Kendaraan di Indonesia: Pengembalian Dana Refund Pasca Jual Beli Kendaraan di Indonesia - Rama Prasja, Teguh; Kurniasih, Esy (UIR Press, 2025)
The practice of buying and selling used vehicles, such as cars, through financing institutions (leasing), often involves various financial components related to consumer transactions, one of which is refund funds. In practice, refund funds that should be given to customers are not always given to customers, but in some cases are transferred to showrooms without the customer's consent or knowledge. This condition raises legal issues related to the protection of consumer rights and legal certainty regarding the return of refund funds. This study aims to analyze the transfer of financing refund funds to showrooms without consumer consent from a civil law perspective and to examine the legal certainty of refund funds to consumers in motor vehicle financing practices. This study uses a normative legal research method with a statutory and conceptual approach. The results of the study indicate that the transfer of refund funds to showrooms without consumer consent can be qualified as an unlawful act that has the potential to create a defect in the will in the formation of the agreement. In addition, the legal certainty of refund funds to customers can be based on the principle of good faith in the agreement and provisions regarding consumer protection. Therefore, clearer regulations regarding refund funds in the practice of buying and selling vehicles, such as cars, are needed to provide legal certainty and more optimal protection for customers.